Practically valuable properties of the surfactant synthesized by Rhodococcus genus actinobacteria - Pirog, Tatiana; Petrenko, Natalia; Skrotska, Oksana; Paliichuk, Olesia; Shevchuk, Tetiana; Iutynska, Galyna (My University, 2020)
Currently, microbial surfactants are the objects of intense research because of their surface-active and emulsifying properties, high antimicrobial, anti-adhesive activity, and ability to destroy biofilms. The review provides current literature data on the properties of surfactants synthesized by Rhodococcus genus actinobacteria, determining their practical significance. The researchers’ interest in the surfactants of Rhodococcus bacteria is primarily due to their key role in the destruction of xenobiotics (aliphatic, heterocyclic and polycyclic aromatic hydrocarbons). Information on the antimicrobial and anti-adhesive activity of surfactants of Rhodococcus genus bacteria remains scarce at present, while the immunomodulatory properties of these products of microbial synthesis are studied more actively than for other microbial surfactants known in the world. The data of our experimental studies on the practically valuable properties of surfactants synthesized by Rhodococcus erythropolis IMV Ac-5017 are presented. Unlike surfactants of other representatives of Rhodococcus genus bacteria, surfactants of IMV As-5017 strain are multifunctional preparations. Because in addition to the high efficiency of the destruction of oil pollution, including complex with heavy metals, surfactants are characterized by high antimicrobial and anti-adhesive activity, including the ability to destroy biofilms.
Keywords: поверхнево-активні речовини; ксенобіотики; антимікробна активність; біоплівки; імуномодулюючі властивості; Rhodococcus erythropolis; surfactants; xenobiotics; antimicrobial activity; biofilms; immunomodulatory properties; кафедра біотехнології і мікробіології